Characteristics of intracellular proteolytic activities of Bacillus megaterium - Moravcová, J; Chaloupka, J (Folia microbiologica, 1990)
Intracellular proteolytic activities of B. megaterium KM occur soluble in the cytoplasm and periplasm and insoluble in the membrane. Two proteolytic enzymes were found in the cytoplasmic fraction by gel filtration on Sephadex G 150 and by polyacrylamide gel electrophoresis. The first enzyme called CI was stable, had a relative molecular mass of Mr = 105,000 (M = 105 kg/mol) and was inhibited by EDTA and PMSF, whereas the second, designated CII, was labile and had a relative molecular mass of Mr = 46,000 (M = 46 kg/mol). Because of its lability it could not be characterized in detail. In the "periplasm" only a single proteolytic enzyme P (Mr = 28,000; M = 28 kg/mol) inhibited by EDTA could be demonstrated. The extracellular enzyme exhibited similar properties. The membrane proteolytic activity was sensitive to PMSF and EDTA. The membrane enzymes have not yet been solubilized. In cells of the mutant KM 12 that does not produce the extracellular proteinase, only one type of proteinase, in all its properties identical with the cytoplasmic proteinase CI, could be demonstrated.
Keywords: mutace; endopeptidasy; Electrophoresis, Polyacrylamide Gel; gelová chromatografie; Endopeptidases; Chromatography, Gel; Mutation; elektroforéza v polyakrylamidovém gelu; Bacillus megaterium